AKS 시민의식 조사도구의 브랜드화 및 활용 방안 - 윤영돈; Young Don Yoon (윤리연구, 1(106), 2016)
본 연구는 한국학중앙연구원(AKS) 시민의식 조사도구 및 실태조사의 브랜드화 및 활용 방안을 다룬 연구이다. AKS 시민의식 조사도구는 ``도덕성에 기반한 시민성`` 실태조사라는 진단도구의 성격을 지니고 있다. 본 조사도구는 시민성, 도덕성, 도덕적 기반(유형)을 제작 준거로 삼고 있으며, 공통 가치지향, 한국 전통적 가치지향, 국가공동체 의식, 국제 및 다문화의식, 가치판단의 준거 등 총6개 범주로 구성되어 있다. 브랜드에 대한 인지도와 이미지가 일종의 자산 가치를 갖는다고 할때, AKS 시민의식 조사도구의 브랜드화는 한국인의 시민의식을 진단하여 그 실태를 파악하고, 시민의식 제고에 기여할 수 있는 자산 가치를 증진시킬 수 있다. AKS 시민의식 조사도구의 브랜드화를 위해 인터넷 홈페이지 및 소셜네트워크서비스(SNS)를 효과적으로 활용할 필요가 있다. 홈페이지를 통한 브랜드 홍보 준거로 접근 가능성, 정보제공, 외국어 서비스, 쌍방향 커뮤니케이션, 시각적 홍보를 들수 있다. AKS 시민의식 조사도구 및 실태조사의 활용 방안으로 먼저 시민의식 조사결과에 근거한 교육적 처방을 들 수 있고, 민주시민교육의 주체이자 모델링의 대상이 될 예비교원 및 군간부를 양성하는 기관(교육대학 및 사범대학, 사관학교및 부사관학교 등)에서 본 조사도구의 사용을 권장할 필요가 있다. 더 나아가 국가 유관기관(국방부, 교육부, 통일부, 국가보훈처 등)을 통한 지속적인 홍보와 로데이타 축적 및 분석자료 조사결과에 대한 피인용지수를 제고할 필요가 있다. 이를 통해 AKS 시민의식 조사도구가 한국인의 시민의식을 진단할 뿐만 아니라 사회문화적·교육적 처방을 통하여 시민의식 제고에 기여할 수 있을 것으로 기대한다. This study discusses the brandization & educational application of Korean value survey supported by Academy of Korean Studies Research Grant. AKS Korean value survey(AKS-KVS) carries the characteristic of citizenship survey based upon morality. This survey counts citizenship, morality, moral foundation(type) as construct criteria and consists of common value, Korean traditional value, national community, international relations & multiculturalism, criteria of value judgment. Just as cognition & image of brand creates a kind of brand equity value, so the brandization of AKS-KVS plays a meaningful role to diagnose & enhance Korean citizenship. With a view to brandizing AKS-KVS, we need to utilize effectively internet homepage & Social Network Service(SNS). Brand PR criteria through homepage run as follows: possibility of access, providing information, foreign language service, two way communication, visual PR. AKS-KVS can be applicable to diagnosing & educating citizenship. And education & training institutions for teacher and commissioned & noncommissioned officer need to use AKS-KVS, who are not only the subject but also the model of democratic civic education. Furthermore, country-related institutions such as Ministry of National Defense, Ministry of Education, Ministry of Unification, Ministry of Patriots and Veterans Affairs etc. can provide raw & analysis data and increase citation frequency. And AKS-KVS can contribute to diagnosing & raising civic value consciousness by means of socio-cultural & educational prescriptions.